Implementation of pancasila values to improve tolerance between religions and tribes - Ilmi, Muhammad Bahrul; Akbar Siregar, Hanfiandi; Rafli Chesio, Muhammad (Universitas Tanjungpura, 2024)
This study aims to evaluate the implementation of Pancasila values in increasingtolerance between religions and ethnicities at SMPN 35 Medan. Pancasila as thefoundation of the Indonesian state contains values that support diversity and socialharmony. However, challenges in creating an environment of tolerance in schools stilloften arise. This study uses qualitative methods with interview and observationtechniques to identify how Pancasila values are applied in the curriculum and schoolactivities. The results of the study indicate that the implementation of Pancasila values,such as Belief in the One Almighty God, humanity, unity, and social justice have had apositive impact on relationships between students from different religious and ethnicbackgrounds. Activities such as interfaith dialogue, cultural activities, and charactereducation programs have proven effective in strengthening mutual respect andunderstanding. This study suggests that other schools can emulate the successfulstrategies at SMPN 35 Medan to create a more inclusive and harmonious environment.